Submission on Specific Aspects of the Elected Presidency - LEE, Jack Tsen-Ta (Institutional Knowledge at Singapore Management University, 2016)
This submission, to which minor redactions have been made, was prepared in response to a call for public feedback (archived here) by the Constitutional Commission to study and make recommendations on specific aspects of the Elected Presidency chaired by the Honourable Chief Justice Sundaresh Menon.